Development of mobile application cinema e-ticket and payment system. - Liew, Mabellyn Linzhen (2021)
There are some problems with the cinema ticketing. This first problem is time-consuming. It will take longer time for users to buy cinema ticket at cinema counter. This is because of they need to queue up for at least 15 minutes to buy a ticket especially at the cinema which located inside shopping mall. The next problem is there are no notifications come out when the tickets are sold out. Customers need to always go to cinema counter to check the available time of some famous movies as the movie maybe sold out. The last problem is the payment method. In the year of 2020, many customers prefer e-payment rather than cash as the corona virus will be spread through everything when that thing being touched by someone. This project is a development of mobile application cinema e-ticket and payment system. In this mobile application, users can see the details of movie list such as released date and summary. Uses also can book their movie tickets if the time slot and seat of movie is available. Users can make their payment through e-payment system such as e-wallet and debit card. When the users successfully book the ticket, the seat available for the movie will be updated and user also can see their receipt through history and email. The system will push up a notification to notify the users before 3 hours the movies starts. Admin can update the movie list such as add and delete the movie list by using this mobile application. Admin can generate report that contains the total sales of certain movie on particular week or month. By using this system, users will have more time to do their things as they no need to queue up at cinema counter.